Building bricks with phase change material (PCM): Thermal performances. (1st February 2021) - Mahdaoui, Mustapha; Hamdaoui, Said; Ait Msaad, Abdelouahad; Kousksou, Tarik; El Rhafiki, Tarik; Jamil, Abdelmajid; Ahachad, Mohammed
Highlights: The thermal behavior of a brick-wall impregnating a PCM was modeled and simulated. Thermal response of the brick with PCM was assessed under summer climatic conditions. A parametric study was conducted to improve the brick behavior and optimize PCM mass. The aim was reinforcing the storage capacity and insulation power of this building element. Integrating PCM in the brick induces better stabilization of the inner surface temperature. Abstract: In certain Moroccan regions, weather conditions are extreme; the outside ambient temperature varies between 45 °C during the day and 25 °C at night in the estival period. Under such conditions, residential and tertiary buildings, which have lightweight walls, may be vulnerable to internal overheating. Heat waves penetrating the building lead to occupant's discomfort and dissatisfaction. Creating an internal climate, which is independent or slightly dependent on external conditions, can be an appropriate solution to mitigate temperature fluctuations. The adoption of new approaches to improve the thermal inertia of lightweight walls is currently among the most widely accepted techniques in literature. In this study, the integration of phase change material (PCM) in building hollow bricks (widely used in Morocco construction) is proposed to improve the thermal performance of external walls. High latent heat of fusion of PCMs will help to dampen the heat flow through the envelope. Physical modeling and numerical analysis of heat transfer through the hollow bricks containing PCM has been carried out. A parametric study was conducted to evaluate the effect of weather conditions on the thermal response of this building element, also the influence of PCM properties are studied and discussed. It is found that the use of PCM in building bricks stabilizes and reduces the indoor temperature fluctuation.